The Role of Micronutrients in the Pathogenesis of Alcohol-Related Liver Disease. (7th September 2021) - Nicoll, Ruairidh; Gerasimidis, Konstantinos; Forrest, Ewan
Abstract: Aims: Chronic alcohol consumption may result in liver injury and chronic liver disease, but other factors are likely to influence disease progression. Malnutrition, specifically micronutrient deficiency, is frequently associated with both alcohol use disorder and chronic liver disease. We hypothesize that micronutrient deficiencies may affect the progression of liver disease in this population. Methods: Systematic integrative review of the medical literature; electronic search of MEDLINE 1950–2021; studies investigating role of any micronutrient in the acceleration of alcohol-related liver injury in humans or animals. Studies which specifically related to alcoholic hepatitis were excluded. Outcomes were extracted and recorded in tabulated form and discussed narratively. Results: We identified 46 studies investigating the role of micronutrient deficiencies in the pathogenesis of alcohol-related liver disease. Specific micronutrients which were identified included folic acid or related B vitamins ( n = 9 studies), Vitamin D ( n = 9 studies), magnesium ( n = 8 studies), zinc ( n = 8 studies) and selenium ( n = 12 including one systematic review). Observational evidence suggests a potential role of magnesium deficiency in accelerating alcohol-related liver injury with weak or negative evidence for other micronutrients. Conclusions: Magnesium deficiency may increase the risk of alcohol-related liver injury and adverse liver outcomes. However, currently, there is insufficient evidence to support magnesium supplementation except for clinically relevant magnesium deficiency. Long-term prospective cohort studies assessing the impact of micronutrients on liver disease progression in patients with alcohol use disorder are lacking and may help determine whether there is a causal role for micronutrient deficiencies in alcohol-related liver injury. Abstract : Short Summary: Micronutrients play a key role in various metabolic processes relevant to alcohol-related liver injury. Basic science and observational human studies support a role for magnesium deficiency in the exaggeration of alcohol-related liver injury. Evidence that other micronutrients affect alcohol-related liver injury is weak.